PREVALENCE OF DECREASED VISUAL ACUITY IN ELEMENTARY SCHOOL-AGE CHILDREN PATIENTS AT KUTIME HEALTH CENTER, TOLIKARA DISTRICT, PAPUA PEGUNUNGAN PROVINCE - Ferdiansyah, Muhammad; Vianny, Audra Lovita; Daeli, P. Rahmat; Nugroho, M. Dwi (Majalah Oftalmologi Indonesia, 2023)
Introduction: Vision has an important role in a child's learning process, and has a correlation with a child's achievement at school. The aim of this study was to determine the prevalence of decreased visual acuity or refractive errors in primary school-age children in the working area of the Kutime Health Center, Nabunage District, Tolikara Regency. Methods: This research is descriptive in nature with a cross-sectional research design and a total sampling technique. The sample for this study were all pediatric patients aged 6-12 years who went to the Kutime Health Center during the period June 2022 to December 2022. Examination of visual acuity in this study used the Snellen Chart. Results: Participants totaled 105 children with prevalence of decreased visual acuity at the Kutime Health Center at 5.71%. The prevalence is higher in girls (6.81%) than boys (4.91%). Based on the affected eyes, the left eye (5.71%) obtained refractive error more than the right eye (3.8%). Decreased vision found in this study was 6/15, 6/12, 6/10, and 6/7.5 which means it is included only in the category of mild vision loss. There were no children (0%) who experienced a moderate and severe decrease in visual acuity in the right or left eye. There were no children (0%) who experienced a profound reduction, reduced visual acuity to near blindness, and blindness without light perception in the right or left eye. The most common age range for children is in the age range of 10-12 years (7.89%). Most of the children with decreased visual acuity came from the village of Kabelogok (12.5%). Conclusion: The prevalence rate of eye disorders in the Kutime Health Center, Nabunage District, Tolikara Regency is 5.71%, this figure is still above the Papua Province rate, which is 2.4% and nationally, which is 4.6%. Advice that can be given to parents and the school is to carry out routine screening in order to be able to detect decreased visual acuity in children's eyes early so that they can be intervened more quickly so as not to exacerbate children's decreased visual acuity in the future.